Plan estratégico de marketing para la comercializadora de vehiculos Autoshow en la ciudad de Loja - Peña Chamba, Rolfi Javier (2022)
The main objective of this research work was to develop a strategic marketing plan for the vehicle marketing company "AUTOSHOW" in the city of Loja. To develop this research, the deductive and inductive method, the analytical method and the synthetic method were used; Surveys were used, which were addressed to customers and workers, as well as an interview with the company manager. 57 surveys were applied to the company's clients in the city of Loja and 2 surveys for the workers who currently work, due to the effect of Covid 19, these were applied online with the help of google forms, they were tabulated and presented with their respective tables, analysis and interpretation. The internal analysis of the company was carried out, where the situation of the company and a mixture of the marketing Mix were diagnosed, concluding this, the matrix of internal factors (EFI) was carried out, where the quality of its vehicles and the legal guarantee they offer, on the other hand, in the most important weaknesses are the lack of advertising and the lack of use of social networks, together with the poor geographical location of its facilities. Next, the external analysis was carried out where the companies that lead the market in the automotive sector in the area were identified, which are Mp Vehicles and Santiago Motors; the company under study is in position 4 out of 5. With all this, it was possible to carry out the matrix of external factors (EFE), where the main opportunities are the reactivation of the automotive market and the increase in preference for acquiring their own vehicle, on the other hand, the most significant threats are the increase in poverty and the strong competition that exists. Finally, it is concluded that the company has not launched a strategic marketing plan to improve and be a benchmark in the automotive market of the city of Loja, nor does it have an institutional philosophy, so they are not clear about the objectives and goals that wants to fulfill in the future